Self-Paced Learning: Islamic Religious Education Learning Method in Elementary School during COVID-19 Pandemic - Efi Tri Astuti; M Fahmi Maulana; Hussein Saadi Mohammed Ali (Program Studi PGMI UIN Salatiga, 2022)
Teachers must be creative educators and be able to choose the right learning methods. This study aims to describe the implementation of the Self-Paced Learning method in Islamic Religious Education (PAI) learning at SDN Pucangsewu, Pacitan District, Pacitan Regency. This study uses a qualitative approach, with a descriptive qualitative approach. The results of the study indicate that the application of the Self-Paced Learning method in Islamic Religious Education learning can help students increase enthusiasm, response, material understanding, and learning outcomes for fourth and fifth grade students. The application of this method is very relevant to the conditions of the physical distance policy. This method has the concept of independent learning with flexible time and is in accordance with Islamic Religious Education material. The learning media used include YouTube, Website, WhatsApp, and E-Books. The teacher provides material through media that is in accordance with the material during face-to-face learning at school. The evaluation process is carried out according to the provisions of the 2013 curriculum. Besides having a positive impact on students, it also has an impact on teachers, namely increasing teacher creativity. However, the application of this method has drawbacks, depending on the availability of mobile devices.